Improvement of Students' Assignment Habit in Mathematics: An Action Research - Adhikari, Khadak Raj (Academic Journal of Mathematics Education, 2024)
In the beginning of the academic year 2022/2023, majority of the students did not complete their assignment on time. So, this action research was carried out to improve the assignment (homework) habit of the sixth-grade students in mathematics classroom. Initially, open questions were given to the students to write the cause of not completing their assignment. The main problems were; students lacked practice, did not manage time for multiple assignment, lacked confidence to do assignment, forgetting assignment, spent maximum time in digital devices and did not get parental help to do the assignment. The assignment was seen and checked regularly throughout the year. 75.6% of the students had always done their assignment, 21.95% of the students has mostly done their assignment, 2.43% of the students sometimes done their assignment, none of the students done their assignment occasionally and no students have found never doing assignment at the end of the term III. After the regular treatment for couple of months students have done their assignment regularly and on time. Finally, it was seen that there was good impact of assignment habits on the performance of students in mathematics. I recommend mathematics teacher to provide less and known assignment in the initial phase to form the habit of doing assignment of students.